Tissue 2-Hydroxyglutarate and Preoperative Seizures in Patients With Diffuse Gliomas. (23rd November 2021) - Ohno, Makoto; Hayashi, Yoshiharu; Aikawa, Hiroaki; Hayashi, Mitsuhiro; Miyakita, Yasuji; Takahashi, Masamichi; Matsushita, Yuko; Yoshida, Akihiko; Satomi, Kaishi; Ichimura, Koichi; Hamada, Akinobu; Narita, Yoshitaka
Abstract : Background and Objectives: Mutant isocitrate dehydrogenase ( IDH ) 1/2 gene products gain a new ability to produce D-2-hydroxyglutarate (D2HG). IDH1/2 mutations are thought to be associated with seizures owing to the structural similarity between D2HG and glutamate. However, the effects of D2HG on seizures in clinical settings are not fully understood. We sought to investigate the relationship between tissue 2-hydroxyglutarate (2HG) concentration and preoperative seizures using clinical samples. Methods: We included 104 consecutive patients with diffuse glioma who underwent surgery from August 2008 to May 2016 and whose clinical presentation and IDH1/2 status were identified. The presence of preoperative seizures, tumor location, histopathologic diagnosis, IDH1/2 status, and 1p/19q codeletion were assessed from the patient charts. Tissue 2HG concentration was measured using liquid chromatography–tandem mass spectrometry. To evaluate 2HG distribution without artefactual tissue disruption, we applied matrix-assisted laser desorption/ionization high-resolution mass spectrometry imaging (MALDI-MSI) in 12 patients' surgically resected samples. We assessed the correlation of preoperative seizures with tissue 2HG concentration, IDH1/2 status, WHO grade, and 1p/19q codeletion. Results: Tissue 2HG concentration was higher in IDH1/2 mutant tumors ( IDH -Mut, n = 42) than in IDH1/2 wild-type tumors ( IDH -WT, n = 62) (median 4, 860 ng/mg vs 75 ng/mg) ( p < 0.0001). MALDI-MSI could detect 2HG signals in IDH -Mut, but not in IDH -WT. Preoperative seizures were observed in 64.3% of patients with IDH -Mut and 21.0% patients with IDH -WT ( p < 0.0001). The optimal cutoff value of tissue 2HG concentration for predicting preoperative seizures was 1, 190 ng/mg, as calculated by the receiver operating characteristic curve. Increased preoperative seizure risk was only observed in tumors with 2HG concentration above the cutoff value among IDH -Mut ( IDH -Mut with above the cutoff value: 71.4% vs IDH -Mut with below the cutoff value: 28.6%; p = 0.031). Multivariate analysis, including IDH1/2 mutation status, tissue 2HG concentration, WHO grade, and 1p/19q codeletion, revealed that only increased tissue 2HG concentration was associated with preoperative seizures (odds ratio 5.86, 95% confidence interval 1.02–48.5; p = 0.048). Discussion: We showed that high tissue 2HG concentration was associated with preoperative seizures, suggesting that excess 2HG increases risk of preoperative seizures in IDH1/2 mutant tumors.